Habitus Generasi Z Dalam Memaknai Kesuksesan Melalui Pendidikan Tinggi Di Kampung Bungaraya - Ajeng Atikah Merlinda; Hesti Asriwandari; Mita Rosaliza (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This study is motivated by the changing orientation of Generation Z toward higher education in rural agrarian areas, particularly in Bungaraya Village, Siak Regency. Higher education, which has traditionally been viewed as a key instrument of social mobility, is now experiencing a legitimacy crisis due to its mismatch with labor market realities. This research aims to analyze the meaning of success among Generation Z, examine the formation of their habitus, and identify forms of social criticism toward higher education. This study employs a qualitative approach with a descriptive method through in-depth interviews, observation, and documentation. Informants consist of Generation Z and parents in Bungaraya Village. The findings reveal a shift in the meaning of success from academic-oriented to pragmatic orientation based on experience, skills, and economic independence. The habitus of Generation Z is shaped by agrarian environments emphasizing practical work rather than formal educational symbols. Social criticism arises due to high education costs, lack of curriculum relevance, and limited job opportunities. This study concludes that higher education is no longer perceived as the only path to success, but rather as one of many alternative choices.